Effect of molecule dipolemoment on hole conductivity of polycrystalline anthrone and anthrachinone layers. - Kania, Sylwester; Kościelniak-Mucha, Barbara; Kulinski, Janusz; Słoma, Piotr (Wydawnictwo Politechniki Łódzkiej, 2015)
Complex analyzes were made using methods of molecular quantum mechanics to investigate the effect of the dipole moment of the molecule carrier drift mobility in polycrystalline layers composed of anthrone and anthrachinone molecules. The differences in the measured mobility values seems to be originated in the variations of the geometry of the frontier orbitals rather than the differences inherent in the crystal arrangement of these molecules, which after all, for both are nearly identical.

Dokonano złożonej analizy, wykorzystując metody kwantowej mechaniki molekularnej dla zbadania wpływu obecności momentu dipolowego molekuły antronu i molekuły antrachinonu na ruchliwość ładunków w warstwach polikrystalicznych zbudowanych z takich molekuł. Źródłem zróżnicowania uzyskiwanych w pomiarze wartości ruchliwości wydaje się być w pierwszym rzędzie różnica geometrii zewnętrznych orbitali molekularnych dla obu badanych molekuł, a nie różnica tkwiąca w uporządkowaniu krystalicznym tychże molekuł, która dla obu jest bardzo podobna, gdyż oba związki krystalizują w identycznej strukturze C2h5(P21/a).
Wpływ momentu dipolowego na przewodnictwo dziur w warstwach polikrystalicznego antronu i antrachinonu.
Institute of Physics, Faculty of Technical Physics, Information Technology and Applied Mathematics. Lodz University of Technology
Instytut Fizyki, Wydział Fizyki Technicznej, Informatyki i Matematyki Stosowanej, Politechnika Łódzka
Centre of Mathematics and Physics, Lodz University of Technology
Centrum Nauczania Matematyki i Fizyki, Politechnika Łódzka
Keywords: polycrystalline films; quasi amorphous films; amorphous films; anthrone; anthrachinone; hole drift mobility; carrier transport; TD-DFT; molekuła antronu; molekuła antrachinonu; kwantowa mechanika molekularna